An Energy Management and Recommender System for Lighting Control in Internet-of-Energy enabled Buildings. Issue 4 (2019) - Kaur, Evaneet; Sharma, Sumedha; Verma, Ashu; Singh, Mukesh
Abstract: Rising trend in urbanization has resulted in the emergence of buildings as major energy consumers. This has increased the burden on the grid which may eventually result into increment of gap between generation and demands. In order to address this problem, the current work focuses on developing nearly zero energy buildings (nZEB) which incorporate distributed generation system and flexible building loads. Accordingly, this work aims to enhance building energy efficiency by retrofitting the electrical components of existing building structures. This includes a real-time monitoring system to track instantaneous power generation and demand to achieve an adequate energy balance in the building, while simultaneously taking suitable energy management and control decisions. The energy optimization and recommendation has been developed as a distributed control system based on multi-agent system architecture, with consideration of maximizing user comfort. The intelligent agents have been developed in JADE and optimization has been performed in MATLAB. The optimization and control signals are relayed to the appliances in an internet-of-energy based environment.